Menstrual Changes after COVID-19 Infection and COVID-19 Vaccination - Işılay Taşkaldıran; Emre Vuraloğlu; Yusuf Bozkuş; Özlem Turhan İyidir; Aslı Nar; Neslihan Başçıl Tütüncü (International Journal of Clinical Practice)
Background. Several factors such as stress, depression, infection, and vaccination influenced the menstrual cycle in women during the coronavirus disease 2019 (COVID-19) pandemic. We investigated whether there were changes in the menstrual cycle in women after COVID-19 vaccination or infection and, if so, the nature of the change. Methods. This study was designed as a descriptive, cross-sectional study. A face-to-face survey was conducted among menstruating women aged 18–50 years from May 31 to July 31, 2022. Women were inquired about their first three menstrual cycles that occurred after COVID-19 infection or vaccination. Results. Of 241 women with COVID-19 infection, 86 (35.7%) mentioned that they experienced various changes in their menstrual patterns in the first three cycles after infection. Of 537 participants who received various COVID-19 vaccines, 82 (15.1%) stated that they experienced changes in their menstrual patterns after vaccination. The incidence of postvaccination menstrual change was higher in women who received Pfizer-BioNTech and Sinovac (CoronaVac) vaccines. Only 10.9% of women who reported a change in their menstrual pattern after vaccination or infection consulted a physician. Conclusion. COVID-19 infection and vaccination can affect the menstrual cycle in women. It is important to be aware of the menstrual changes after COVID-19 infection and vaccination and to warn and inform women about this issue.